L2 fluency in spoken interaction: a case study on the use of other-repetitions and collaborative completions - Pauliina Peltonen (My University, 2022)
Second language (L2) speech fluency has usually been studied from an individual’s perspective with monologue speech samples, whereas fluency studies examining dialogue data, especially with focus on collaborative practices, have been rare. In the present study, the aim was to examine how participants maintain fluency collaboratively. Four Finnish upper secondary school students of English completed a problem-solving task in pairs, and their spoken interactions were analyzed qualitatively with focus on collaborative completions and other-repetions. The findings demonstrated that collaborative completions and other-repetitions contribute to interactional fluency by creating cohesion to the interaction. Collaborative completions were also used to help the interlocutor to overcome temporary (individual) disfluent phases. Overall, the findings suggest that individual and interactional fluency are intertwined in spoken interaction, which should be acknowledged in theoretical approaches to L2 fluency and in empirical studies examining L2 fluency in interactional contexts.